Outstanding Surface Passivation for Highly Efficient Silicon Solar Cells Enabled by Innovative AlyTiOx/TiOx Electron‐Selective Contact Stack. Issue 10 (16th August 2022) - Shehata, Mohamed M.; Phang, Pheng; Basnet, Rabin; Yin, Yanting; Kremer, Felipe; Bartholazzi, Gabriel; Andersson, Gunther G.; Macdonald, Daniel H.; Black, Lachlan E.
Abstract : Passivating contacts based on transition metal oxides (TMOs) have the potential to overcome existing performance limitations in high‐efficiency crystalline silicon (c‐Si) solar cells, which is a significant driver for continuing cost/Watt reductions of photovoltaic electricity. Herein, innovative stacks of Al‐alloyed TiO x (Al y TiO x ) and pure TiO x as transparent electron‐selective passivating contacts for n‐type c‐Si surfaces are explored. An optimized stack of 2 nm Al y TiO x and 2 nm TiO x is shown to provide both record‐quality surface passivation and excellent electrical contact, with a surface recombination current density prefactor J 0 of 2.4 fA cm −2 and a specific contact resistivity ρ c of 15.2 mΩ cm 2 . The performance of this innovative stack significantly exceeds previously reported values for pure or doped TiO x single layers, SiO x /TiO x stacks, a‐Si:H/TiO x stacks, and other transparent contact technologies. Furthermore, an excellent efficiency of 21.9% is attained by incorporating the optimized stack as a full‐area rear contact in an n‐type c‐Si solar cell. The findings set a new benchmark for the passivation performance of metal oxide‐based passivating contacts, bringing it to a level on par with state‐of‐the‐art SiO x /poly‐Si contacts while greatly improving optical transparency. Abstract : Herein, outstanding surface passivation combined with very low contact resistivity on silicon using a highly transparent stack of Al‐alloyed and pure TiO x (Al y TiO x /TiO x ) is demonstrated. The optimized stack's surface passivation quality is comparable with that of state‐of‐the‐art SiO x /n + ‐poly‐Si passivating contacts, yielding 21.9% efficiency in a silicon solar cell.